THE EFFECT OF ENVIRONMENT, SOCIAL AND GOVERNANCE ON FIRM VALUE WITH FIRM SIZE AS A MODERATING VARIABLE - Maria Gratia Kolo; Muslichah Muslichah (ZILLZELL MEDIA PRIMA, 2025)
This study examines the effect of Environment, Social, and Governance (ESG) factors on firm value, with company size as a moderating variable, in basic materials and industrials companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Fourteen companies were picked using purposive sampling, resulting in a total of 42 observations. Data were examined utilizing multiple regression and moderated regression analysis (MRA) with SPSS 26. The results demonstrate that ESG as a whole and the environmental component do not substantially affect corporate value; however, the social and governance facets have an effect on firm value. Furthermore, firm size does moderate the influence of ESG and environmental issues on firm value; instead, it moderates the impact of social and governance elements on firm value.